1982
DOI: 10.1088/0022-3727/15/10/011
|View full text |Cite
|
Sign up to set email alerts
|

Transient voltage measurement of primary ionisation in nitrogen

Abstract: Electron impact ionisation of nitrogen gas has been studied using an integrated voltage method with the data subjected to a full analysis including the effects of diffusion. Values of the primary ionisation coefficient have been obtained over the swarm energy range 300 nTd<or=E/N<or=2400 Td. Experimental evidence has been obtained that secondary effects contribute greatly to the charge flow at these high values of E/N and that if not recognised may produce false values of alpha /N. The effect of ignoring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…Recently, some researchers have found that when plates were cycled towards failure, there was a buildup of PbSO4 crystals around the grid member. This was found in plates of Pb-Sb grids (33,47) and in nonantimonial grids (48)(49)(50). As discussed previously, we have observed the same buildup.…”
Section: Density Of Active Materials--dittman and Samsmentioning
confidence: 76%
“…Recently, some researchers have found that when plates were cycled towards failure, there was a buildup of PbSO4 crystals around the grid member. This was found in plates of Pb-Sb grids (33,47) and in nonantimonial grids (48)(49)(50). As discussed previously, we have observed the same buildup.…”
Section: Density Of Active Materials--dittman and Samsmentioning
confidence: 76%
“…As the coefficient γ depends not only on the gas species but also on the material and state of the cathode surface, it is expedient to determine γ under conditions of our experiments. To this end we obtained the dependence of α/p on E/p with the Bolsig numerical code permitting us to find the transport coefficients of electrons in a number of gases with the superimposed electric field E. In this paper we also used the measured and calculated data of [31][32][33][34][35][36] and obtained the approximation formulae…”
Section: Resultsmentioning
confidence: 99%